Pendampingan Penulisan Proposal PKM Berbasis Case Method sebagai Upaya Meningkatkan Literasi Kepenulisan Akademik Mahasiswa PGSD - Unga Utami; Widya Karmila Sari Achmad; Unga Utari; Noer Intan Novitasari; Muh. Rizah Putrawan (Jurnal Abdi Bangsa, 2026)
Students' ability to develop proposals for the Student Creativity Program (Program Kreativitas Mahasiswa/PKM) is an essential competency that supports the advancement of academic writing literacy in higher education. However, students of the Elementary School Teacher Education Program (PGSD) still encounter several challenges, including limited understanding of PKM guidelines, difficulties in identifying relevant and feasible issues to address, and constraints in preparing systematic proposals that meet the required standards. This community service program aimed to enhance the academic writing literacy of PGSD students through case method-based mentoring in PKM proposal writing. The implementation of the program consisted of three stages: preparation, implementation, and evaluation. During the implementation stage, students participated in training sessions, PKM proposal case analyses, group discussions, and intensive mentoring activities until they successfully produced proposal drafts ready for submission. The evaluation stage was conducted by assessing participants’ level of understanding and the quality of the proposals produced. The results demonstrated improvements in students’ understanding of the structure and substance of PKM proposals, enhanced skills in generating creative ideas and preparing proposals in accordance with established guidelines, and the successful completion of PKM proposal drafts deemed suitable for submission to PKM funding schemes. This program contributed positively to strengthening students’ academic writing literacy while also increasing their readiness to participate in the Student Creativity Program competition.